(untitled) (Вісник: Міжнародні відносини, 2024)
The article analyzes the concept of "emotional intelligence", reveals the need for its assessment by the company’s staff and consideration for employment. The socio-psychological research in this area were studied, an analysis of the influence of the EI level on the employee’s performance was carried out, the experience of foreign companies in using the EI factor in their activities was considered. It has been proven that at present, companies of the fourth level of maturity with the highest financial performance, which have made a bet on EI, firstly, have a highly effective potential for recruiting and hiring personnel, including such emotional and psychological characteristics as ambition, learning, passion, and purposefulness. Secondly, they acquire a competitive advantage in the new market conditions associated with global technological challenges and business process management in the context of digitalization and Industry 4.0 in general.